A Mixed-Method Analysis of Continuing Professional Development for EFL Teachers - Ezzeddine Saidi (Journal of English as A Foreign Language Teaching and Research, 2025)
This study explores how Tunisian teachers of English as a Foreign Language (EFL) understand Continuing Professional Development (CPD) and how the in-service training they receive from the inspectors shapes their beliefs about the role(s) of self-explorations in achieving autonomous CPD. It adopts a mixed-method design consisting of a questionnaire answered by 99 EFL teachers working in public schools across the country and interviews conducted with three EFL inspectors from different Regional Directorates of Education. The analysis of the data collected with the two instruments confirms that the preparation areas chosen for the teachers are exclusively determined by the inspectors, with minimum interference from the teachers; the majority of the surveyed teachers link their CPD cycles to the supervision provided by the inspectors; and the inspectors seem to have a deeper understanding of CPD, but they consistently advocate some degree of involvement in the teachers’ self-explorations.